Radiation-resistant nanotwinned austenitic stainless steel. (15th January 2019) - Meric de Bellefon, G.; Robertson, I.M.; Allen, T.R.; van Duysen, J.-C.; Sridharan, K.
Abstract: A key strategy to increase the radiation resistance of materials has been to introduce a high density of interfaces that can act as sinks for radiation-induced defects. Twin boundaries are a type of interface that can be introduced through deformation but are usually considered to be ineffective sinks. Using heavy ion irradiation and transmission electron microscopy, this study investigates the influence of a high area per unit volume of twin boundaries on the radiation-induced swelling response of an austenitic stainless steel. The study shows that swelling can be suppressed in regions containing a high density of closely-spaced deformation twin boundaries. Graphical abstract: Unlabelled Image